Malignant melanoma misdiagnosed as diabetic foot ulcer: A case report. Issue 29 (July 2017) - Gao, Wei; Chen, Dawei; Ran, Xingwu
Abstract: Rationale: Acral lentiginous melanoma (AML) does not exhibit the classic signs of malignant melanoma. ALM is frequently misdiagnosed because of its unusual sites and atypical clinical morphologies, which lead to poor prognosis. Patient concerns: A female patient aged 78 years was presented to our center with two ulcers on her right foot. Diabetic foot ulcer was considered as the primary diagnosis. The ulcers failed to improve after 2 weeks' therapy. Diagnoses: An incisional biopsy of the lesion revealed malignant melanoma. Interventions: The patient received wide excision, skin grafting as well as biotherapy. Outcomes: The lesion was healed and no other metastasis has been founded until now. Lessons: Clinicians must maintain a high level of suspicion in distinguishing malignant melanoma from other more benign skin lesions of the foot. The need for early biopsy of ulcer, even when clinical suspicion is low, can not be overemphasized. Only in this way can we reduce misdiagnosis rate and improve survival rate in patients with foot ulcer.